LINGUOCULTURAL FEATURES AND THEIR CORPUS ANALYSIS OF ENGLISH FEMALE NAMES - Ganiyeva Saodat Abduhafizovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This research is based on linguistic and linguocultural study relatively. There conducted a corpus analysis of 50 English names. In this investigation, the author covered name elements, deep notions in linguistics, cultural cognition. In other words, the study determines religious and historical denotation and root to Old English relevant to male and female names. The gender elements of names lead to Anglo-Saxon dialect. Mostly, English female names are entitled “sister”, “wife”.